Manganese-based layered oxide positive electrode material, preparation method and application
The KxLiyFezMn1-y-zO2 material was prepared by co-substitution and solid-phase reaction method of Fe and Li, which solved the problem of insufficient reversible capacity and circulation capacity of manganese-based layered oxide positive electrode material in potassium ion batteries, and achieved high specific capacity and The effect of long cycle life is suitable for large-scale energy storage applications.
Patent Information
- Application Number
- CN202411665184.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-21
AI Technical Summary
The existing manganese-based layered oxide positive electrode materials have poor reversible capacity and circulation capabilities in potassium ion batteries, and are relatively high in cost, making it difficult to meet the needs of large-scale energy storage.
Through the co-substitution of the active element Fe and the inactive element Li, the KxLiyFezMn1-y-zO2 material is prepared by solid phase reaction method to ensure that the valence state of the Mn element is always +4, inhibit the Jahn-Teller effect, and improve the structural stability of the material and Cyclic performance.
It realizes the high specific capacity and long cycle life of manganese-based layered oxide cathode material, with excellent rate performance, and is suitable for large-scale production and commercial applications.
Smart Images

Figure CN119495738A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of potassium ion batteries and relates to a manganese-based layered oxide positive electrode material, a preparation method and an application thereof. Background Art
[0002] Secondary battery energy storage devices represented by lithium-ion batteries have become the fastest growing energy storage technology in the world due to their advantages such as high energy density, long cycle life, high safety, and environmental friendliness. However, lithium-ion batteries are now facing a severe situation of lithium resource shortage, difficulty in mining, and excessively high battery manufacturing costs, which seriously restricts their further development in the field of large-scale energy storage. It is urgent to develop new secondary ion battery energy storage technologies with low cost, high efficiency, high safety, and high specific energy. Potassium-ion batteries have abundant potassium resources and low cost. They have the same working principle as lithium-ion batteries and similar hydrogen standard potential (-2.94Vvs.SHE). In addition, potassium can be alloyed with graphite negative electrodes, and aluminum can be used as a current collector. Therefore, from the perspective of further reducing production costs, reducing battery weight, and improving energy density, potassium-ion batteries have broad application prospects in the future field of large-scale energy storage. As the core component of potassium-ion batteries, the cost and performance of the cathode material directly determine the overall cost and key performance parameters such as battery energy density and cycle life. Layered oxides have been considered as strong contenders for cathode materials in potassium-ion batteries due to their high theoretical capacity and simple synthesis methods.
[0003] However, although early studies have demonstrated that some layered oxides P-type K x MnO2 has the reversible insertion / extraction of potassium ions, but its reversible capacity and cycle ability are still poor. Replacing the Mn element by element doping has become a widely studied strategy. Although the structural stability can be improved by replacing inactive elements, the specific capacity of the layered oxide will be significantly reduced. The modification of manganese-based layered oxide positive electrode materials in the prior art is still difficult to meet the needs: for example, the invention CN116081694A mixes raw potassium salt, manganese oxide, lithium salt powder and alcohol, presses and sinters; suppresses the structural phase change by doping with the inactive element Li; however, this method cannot effectively suppress the Mn 3+ The Jahn-Teller effect causes structural degradation problems, and only the substitution of inactive elements will significantly reduce the capacity of the positive electrode material. For example, the preparation method disclosed in the invention CN117913266A uses a liquid phase coprecipitation method to prepare the positive electrode material. The coprecipitation method has a long preparation process, and there is still a lot of Mn in the synthesis process. 3+Therefore, its best performance after 100 cycles is only 80% capacity retention. In addition, as disclosed in the invention CN202410584587.9, K x MnO2 and annealing at high temperature to achieve the purpose of inhibiting the dissolution of transition metals; however, this method is extremely costly and has low yield, making it difficult to commercialize.
[0004] Therefore, how to achieve high specific capacity while maintaining long cycle life is a technical problem that needs to be urgently solved in the development of potassium ion batteries. Summary of the invention
[0005] The key reason for the structural instability of manganese-based layered oxide cathode materials is that Mn 3+ The severe Jahn-Teller distortion not only induces transition metal layer slip and crystal structure distortion during potassium storage, but also generates easily soluble Mn 2+ , accelerating the dissolution of transition metal ions in the electrolyte, resulting in the loss of active materials. On the other hand, at high voltage, the positive electrode material has a serious irreversible phase change. Therefore, the key to improving manganese-based layered oxide positive electrode materials is to reduce the Mn content in the initial material. 3+ The present invention prepares a new material K by co-substituting the active element Fe and the inactive element Li using a simple solid phase reaction method. x Li y Fe z Mn 1-y-z O2, in the preparation process, the valence state of Mn element is always kept at +4, which inhibits the structural distortion caused by Jahn-Teller effect and effectively alleviates the 3+ The problem of Mn element dissolution caused by disproportionation reaction.
[0006] The technical solution adopted by the present invention to solve the technical problem is: a manganese-based layered oxide positive electrode material, the chemical formula of the positive electrode material is: K x Li y Fe z Mn 1-y-z O2, wherein 0.3≤x≤0.7, 0<y≤0.3, 0<z≤0.3; the positive electrode material is a potassium ion battery manganese-based layered positive electrode material synthesized by solid phase reaction method using K source, Li source, Fe source and Mn source as raw materials; the particle size of the manganese-based layered oxide positive electrode material is 0.5-10μm. The present invention firstly adopts the solid phase reaction method to directly synthesize the manganese-based layered positive electrode material, and uses the method of co-doping of Li and Fe elements and adjusting the content of K element to ensure that the valence state of Mn element in the layered oxide is always kept at +4, thereby eliminating Mn 3+The Jahn-Teller effect brought about by this can improve the material capacity, cycle and rate performance of manganese-based layered oxides. The inactive Li element can stabilize the lattice and improve the structural stability. The active element Fe can provide redox ability in the cycle process, reduce the redox of Mn in the discharge process, and thus make the Mn generated in the discharge process 3+ The content is reduced. By co-substitution of active elements and inactive elements, the battery specific capacity is guaranteed while the cycle stability is improved. Therefore, the present invention is simple to operate, easy to repeat, and has a short production cycle, and is suitable for large-scale production of manganese-based layered oxide positive electrode materials for potassium ion batteries.
[0007] Preferably, the K source includes: at least one of potassium carbonate, potassium hydroxide, and potassium bicarbonate; the Li source includes: at least one of lithium carbonate and lithium hydroxide; the Fe source includes: at least one of ferric oxide and ferroferric oxide; the Mn source includes: at least one of manganese dioxide, manganese tetraoxide, manganese trioxide, and manganese monoxide; wherein the content of the K element is regulated so that the Mn element in the chemical formula maintains a valence of +4.
[0008] The present invention also discloses a method for preparing a manganese-based layered oxide positive electrode material, which is used to prepare the above-mentioned manganese-based layered oxide positive electrode material. The preparation method comprises the following steps:
[0009] Step S1: ball-milling a mixture of a K source, a Li source, a Fe source and a Mn source in proportion to obtain a mixed material;
[0010] Step S2: calcining the mixture prepared in step S1 to obtain a manganese-based structured oxide positive electrode material.
[0011] The manganese-based layered oxide positive electrode material obtained by the method of the present invention has good stability and rate performance when used as a positive electrode material for potassium ion batteries. The method is simple to operate, easy to prepare, green and environmentally friendly, and can be applied to the production process of large-scale products.
[0012] Preferably, in step S1, the ball milling speed is 200-600 r / min, and the ball milling time is 2-10 h.
[0013] More preferably, in step S1, the ball milling speed is 300-400 r / min, and the ball milling time is 6-9 h.
[0014] Preferably, in step S2, the calcination is carried out in air or oxygen atmosphere at 800-1200°C for 10-30h; the heating rate of the calcination is 1-10°C / min, and the cooling rate is 1-10°C / min; after the calcination is completed, it is taken out at 20-300°C and stored in a water-free and oxygen-free environment.
[0015] More preferably, in step S2, the calcination is carried out at 850-950°C for 15-24h; the heating rate of the calcination is 3-5°C / min, and the cooling rate is 3-5°C / min; after the calcination is completed, it is taken out at 150-300°C and stored in a glove box.
[0016] The present invention also discloses an application of a manganese-based layered oxide positive electrode material, wherein the application adopts the above-mentioned manganese-based layered oxide positive electrode material, and the application is to prepare a potassium ion battery, wherein the potassium ion battery comprises: an active substance, conductive carbon black and PVDF, and the active substance adopts the manganese-based layered oxide positive electrode material.
[0017] Preferably, the mass ratio of the active material, conductive carbon black and PVDF is 7:2:1 to 9:0.5:0.5.
[0018] The beneficial effects of the present invention are:
[0019] The present invention improves the performance degradation problem of manganese-based transition metal layered oxide materials during the cycle process by co-doping with Li and Fe elements; by designing the content of K element in manganese-based layered oxides and replacing Li and Fe elements, the valence state of Mn element is guaranteed to always remain +4, thereby inhibiting the Jahn-Teller effect. At the same time, the inactive element Li is doped to stabilize the lattice, and the doping of Fe element can reduce the redox of Mn element, thereby reducing the occurrence of Mn in the charge and discharge process. +3 Content; When the manganese-based layered oxide positive electrode material of the present invention is applied to the positive electrode of a potassium ion battery, the battery has a higher specific capacity and cycle stability. At a current of 20mA / g, the battery can exert an initial specific capacity of 110.5mA h / g. At a current of 20mA / g, the capacity retention rate is still 90.9% after 100 cycles of charge and discharge. At a current of 1000mA / g, the battery can exert a specific capacity of 57.4mA h / g, with excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is an XRD diagram of the manganese-based layered oxide positive electrode material prepared in Example 2 of a manganese-based layered oxide positive electrode material, a preparation method and an application of the present invention;
[0021] Figure 2 is a SEM image of the manganese-based layered oxide positive electrode material prepared in Example 2 of the present invention;
[0022] Figure 3 This is a cycle diagram of the manganese-based layered oxide positive electrode material prepared in Example 2 of the present invention;
[0023] Figure 4This is a rate diagram of the manganese-based layered oxide positive electrode material prepared in Example 2 of the present invention;
[0024] Figure 5 This is a cycle diagram of the manganese-based layered oxide positive electrode material prepared in Comparative Example 1 of the present invention;
[0025] Figure 6 It is a rate diagram of the manganese-based layered oxide positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Layered cathode materials are one of the most commercially promising sodium ion cathode materials, and can generally be divided into two types: P-type and O-type. Compared with O-type materials, materials with P-type structures tend to have higher average discharge voltages and better rate performance. Figures 1 to 6 As shown, this embodiment starts from P-type structured manganese-based oxides, and first uses Li and Fe to replace Mn during the sintering process to inhibit the large-volume phase transition from the P phase to the O phase and inhibit vacancy ordering, thereby improving the cycle stability of the material and obtaining a variety of manganese-based positive electrode materials.
[0028] Example 1
[0029] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0030] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K:Li:Fe:Mn=0.35:0.1:0.05:0.85, and mix them by ball milling at a speed of 400r / min for 6h, using zirconia balls as the ball milling medium, to obtain a mixture;
[0031] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.35 Li 0.1 Fe 0.05 Mn 0.85 O2;
[0032] Example 2
[0033] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0034] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K:Li:Fe:Mn=0.4:0.1:0.1:0.8, and mix them by ball milling at a speed of 400r / min for 6h, using zirconia balls as the ball milling medium, to obtain a mixture;
[0035] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.4 Li 0.1 Fe 0.1 Mn 0.8 O2;
[0036] Example 3
[0037] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0038] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K:Li:Fe:Mn=0.45:0.1:0.15:0.75, and mix them by ball milling at a speed of 400r / min for 6h, using zirconia balls as the ball milling medium, to obtain a mixture;
[0039] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.45 Li 0.1 Fe 0.15 Mn 0.75 O2;
[0040] Example 4
[0041] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0042] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K:Li:Fe:Mn=0.5:0.1:0.2:0.7, and mix them by ball milling at a speed of 400r / min for 6h, using zirconia balls as the ball milling medium, to obtain a mixture;
[0043] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.5 Li 0.1 Fe 0.2 Mn 0.7 O2;
[0044] Example 5
[0045] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0046] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K:Li:Fe:Mn=0.55:0.15:0.1:0.75, and mix them by ball milling at a speed of 400r / min for 6h, using zirconia balls as the ball milling medium, to obtain a mixture;
[0047] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.55 Li 0.15 Fe 0.1 Mn 0.75 O2;
[0048] Example 6
[0049] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0050] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K: Li: Fe: Mn = 0.7: 0.2: 0.1: 0.7, and mix them by ball milling at a speed of 400 r / min for 6 hours, using zirconia balls as the ball milling medium, to obtain a mixture;
[0051] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.7 Li 0.2 Fe 0.1 Mn 0.7 O2;
[0052] Example 7
[0053] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0054] S1. Put K2CO3, Li2CO3, Fe2O3 and Mn2O3 into a ball mill in order according to the molar ratio of K:Li:Fe:Mn=0.4:0.1:0.1:0.8, and mix them by ball milling at a speed of 400r / min for 6h, using zirconia balls as the ball milling medium, to obtain a mixture;
[0055] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled by 20°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.4 Li 0.1 Fe 0.1 Mn 0.8 O2;
[0056] Comparative Example 1
[0057] The method for preparing a manganese-based layered oxide positive electrode material comprises the following steps:
[0058] S1. Put K2CO3 and Mn2O3 into a ball mill in sequence according to a molar ratio of K:Mn=0.4:1, and mix them by ball milling at a speed of 400r / min for 6h, using zirconium oxide balls as the ball milling medium, to obtain a mixture;
[0059] S2, the mixed material of step S1 was pressed into tablets at 18 MPa, transferred to a muffle furnace and heated to 850°C at a heating rate of 5°C / min, sintered in an air atmosphere for 24 hours, cooled to 300°C at a cooling rate of 5°C / min, and transferred to a glove box for storage to obtain a manganese-based positive electrode material K 0.4 MnO2;
[0060] Application and performance testing
[0061] The potassium ion battery manganese-based layered oxide positive electrode materials prepared in the above examples and comparative examples were used to construct potassium ion button batteries, respectively, and the specific operations were as follows:
[0062] Positive electrode sheet: Grind the positive electrode material, conductive carbon black and PVDF binder in a mass ratio of 7:2:1, add appropriate amount of NMP to make slurry, coat with aluminum foil, dry in a forced air drying oven at 80°C for 1h, dry in a vacuum drying oven at 80°C for 12h, and cut into 10mm round positive electrode sheets;
[0063] Negative electrode: Potassium metal sheet with a diameter of 12mm;
[0064] Diaphragm: Whatman GF / D glass fiber with a diameter of 16 mm;
[0065] Electrolyte: 0.8M KPF6 in EC:DEC (1:1)
[0066] The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled in a glove box filled with high-purity argon to obtain a CR2032 button battery.
[0067] The following electrochemical performance tests were performed on the CR2032 button cells constructed with different potassium ion battery manganese-based layered oxide positive electrode materials:
[0068] Initial discharge capacity and cycle performance test: In a constant temperature box, set the temperature to 25°C and let it stand for 8 hours.
[0069] Table 1 Electrochemical test table of manganese-based layered oxide positive electrode materials of Examples 1-6
[0070]
[0071] It can be seen from Examples 1-4 that Fe doping can provide a higher initial specific capacity.
[0072] It can be seen from Examples 5-6 that doping with the inactive element Li will lead to a decrease in the initial specific capacity, but can improve the cycle stability.
[0073] It can be seen from Example 7 that after the solid phase reaction is completed, cooling to room temperature will significantly reduce the cyclic stability of the material. Taking it out at high temperature and transferring it to a glove box can improve the capacity and cyclic performance of the material.
[0074] It can be seen from Comparative Example 1 that without doping Li and Fe elements, the initial capacity is low and the cycle stability is extremely poor.
[0075] Figure 1 The results show that the structure of the manganese-based layered oxide cathode material obtained by solid phase synthesis maintains the P3 structure with an R-3m space group. The refinement results show that the interlayer spacing is
[0076] Figure 2 The results show that the morphology of the manganese-based layered oxide positive electrode material obtained by solid phase synthesis is lamellar and the particle size is 1-5μm.
[0077] Figure 3 The results showed that K 0.4 Li 0.1 Fe 0.1 Mn 0.8The O2 manganese-based layered oxide positive electrode material has excellent cycle stability and can maintain 84.5% of its capacity after 150 cycles at a current of 60mA / g.
[0078] Figure 4 The results showed that K 0.4 Li 0.1 Fe 0.1 Mn 0.8 The O2 manganese-based layered oxide positive electrode material has excellent rate performance and still has a capacity of 57.4 mA h / g at a current of 1000 mA / g.
[0079] Figure 5 The results showed that K 0.4 The capacity and cycle stability of MnO2 manganese-based layered oxide positive electrode materials are poor.
[0080] Figure 6 The results showed that K 0.4 The rate performance of MnO2 manganese-based layered oxide positive electrode material is poor, with a capacity of only 38.7 mA h / g at a current of 1000 mA / g.
[0081] In summary, the present invention improves the performance degradation problem of manganese-based transition metal layered oxide materials during the cycle process by co-doping with Li and Fe elements; by designing the content of K element in manganese-based layered oxides and replacing Li and Fe elements, the valence state of Mn element is always kept at +4, thereby suppressing the Jahn-Teller effect. At the same time, the inactive element Li is doped to stabilize the lattice, and the doping of Fe element can reduce the redox of Mn element and reduce the occurrence of Mn in the charge and discharge process. +3 When the manganese-based layered oxide positive electrode material of the present invention is applied to the positive electrode of a potassium ion battery, the battery has a higher specific capacity and cycle stability and has excellent rate performance. Therefore, the present invention has broad application prospects in the field of potassium ion battery technology.
[0082] It should be emphasized that the above are only preferred embodiments of the present invention and do not impose any form of limitation on the present invention. Any simple modification of the above embodiments based on the technical essence of the present invention also falls within the protection scope of the present invention. Other equivalent changes and modifications still fall within the scope of the technical solution of the present invention.
Claims
1. A manganese-based layered oxide positive electrode material, characterized in that: The chemical formula of the positive electrode material is: K x Li y Fe z Mn 1-y-z O2, wherein 0.3≤x≤0.7, 0<y≤0.3, 0<z≤0.3; the positive electrode material is a manganese-based positive electrode material for potassium ion batteries synthesized by a solid phase reaction method using K source, Li source, Fe source and Mn source as raw materials.
2. A manganese-based layered oxide positive electrode material, characterized in that: The K source includes at least one of potassium carbonate, potassium hydroxide, and potassium bicarbonate; the Li source includes at least one of lithium carbonate and lithium hydroxide; the Fe source includes at least one of ferric oxide and ferroferric oxide; the Mn source includes at least one of manganese dioxide, manganese tetraoxide, manganese trioxide, and manganese monoxide.
3. A method for preparing a manganese-based layered oxide positive electrode material, characterized in that: The method is used to prepare the manganese-based layered oxide positive electrode material according to any one of claims 1 to 2, and the method comprises the following steps: Step S1: ball-milling a mixture of a K source, a Li source, a Fe source and a Mn source in proportion to obtain a mixed material; Step S2: calcining the mixture prepared in step S1 to obtain a manganese-based structured oxide positive electrode material.
4. The method for preparing a manganese-based layered oxide positive electrode material according to claim 3, characterized in that: In the step S1, the rotation speed of the ball mill is 200-600 r / min, and the ball milling time is 2-10 h.
5. The method for preparing a manganese-based layered oxide positive electrode material according to claim 4, characterized in that: In the step S1, the rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 6-9 h.
6. The method for preparing a manganese-based layered oxide positive electrode material according to claim 3, characterized in that: In the step S2, calcination is carried out in air or oxygen atmosphere at 800-1200°C for 10-30h; the heating rate of calcination is 1-10°C / min, and the cooling rate is 1-10°C / min; after calcination, it is taken out at 20-300°C and stored in a water-free and oxygen-free environment.
7. The method for preparing a manganese-based layered oxide positive electrode material according to claim 6, characterized in that: In the step S2, the calcination is carried out at 850-950°C for 15-24h; the heating rate of the calcination is 3-5°C / min, and the cooling rate is 3-5°C / min; after the calcination is completed, the calcination is carried out at 150-300°C and stored in a glove box.
8. An application of a manganese-based layered oxide positive electrode material, characterized in that: The application adopts the manganese-based layered oxide positive electrode material described in any one of claims 1 to 2, and the application is to prepare a potassium ion battery. The potassium ion battery comprises: an active substance, conductive carbon black and PVDF, and the active substance adopts the manganese-based layered oxide positive electrode material.
9. The use of a manganese-based layered oxide positive electrode material according to claim 8, characterized in that: The mass ratio of the active material, conductive carbon black and PVDF is 7:2:1 to 9:0.5:0.5.
Citation Information
Patent Citations
Electrode materials comprising a layered oxide that contains potassium and a metal, electrodes comprising said materials and use thereof in electrochemistry
CN113906585A
Potassium ion supported synergistic heterogeneous element doped sodium ion battery positive electrode material and preparation method and application thereof
CN115881939A
Preparation method of lithium-doped manganese-based layered oxide for positive electrode material of potassium ion battery
CN116081694A
Manganese-based quaternary transition metal oxyfluoride as well as preparation method and application thereof
CN118676359A
Doped and modified P3-phase sodium-ion battery manganese-based layered positive electrode material as well as preparation method and application thereof
CN118867220A